Поединок: повесть / А. И. Куприн ; худ. П. Пинкисевич - Куприн Александр Иванович (Школьная библиотека, 1984)
Экземпляры: (20170307) / Инвентарный номер: 13418 / Цена: 0.65 / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: К 92 / ББК: 84(2Рос=Рус)1